A QoS awareness scheme sustaining seamless handover for network mobility - Hussien, Loay Faisal; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hassan, Wan Haslina (2014)
Network Mobility (NEMO) basic support protocol (RFC 3963) has been proposed by Internet Engineering Task Force (IETF) to extend the operation of Mobile IPv6 for providing uninterrupted Internet connectivity to the communicating nodes of mobile networks. The protocol operates by moving the mobility functionality from Mobile IPv6 mobile nodes to a mobile network’s router. This router device is known as a Mobile Router (MR) in the mobile network, which performs binding update with its Home Agent (HA) to establish a bi-directional tunnel between the HA and MR. NEMO is designed with elucidation so that network mobility is transparent to the nodes inside the Mobile Network in order to reduce location update signaling that would occur by each a Mobile Network Node (MNN). Nevertheless, delays in data delivery and higher overheads are likely to transpire because of suboptimal routing and multiple encapsulations of data packets. Therefore, this paper proposes a new scheme using the mechanisms of Fast Hierarchical Mobile IPv6 (FHMIPv6) to reduce location update signaling issues. Furthermore, the proposed scheme introduces the use of DiffServ model to achieve smooth delivery of real-time traffic in heterogeneous mobile networks. Eventually, it aims to minimize the packet loss and diminish the handover latency as well. Keywords: FHMIPv6, NEMO, QoS, DiffServ.